The Role of Thunder in Finnegans Wake. (University of Toronto Press, 1997)
James Joyce's use of ten one hundred-letter words in Finnegans Wake has always been an intriguing feature of that novel. Eric McLuhan takes a new by placing the Wake in the tradition of Menippean satire, where language is used to shock and provoke. Seen in this light, Joyce's peculiar language and style become part of this Menippean tradition through his use of the linguistic 'thunderclap'. The Role of Thunder in Finnegans Wake is the first book to examine this strangest and most prominent aspect of the language of the Wake, and explain its use in the context of classical Greek literature. Each thunderclap is a resonating logos that represents a transformation of human culture. McLuhan presents the thunders as encoding Joyce's study of ten major communications revolutions, ranging from neolithic technologies such as speech and fire, through cities, the railroad, and print, to radio, movies, and television. Seen in this fashion, Finnegans Wake is both an encyclopedia of the effects of technology in reshaping human culture and society, and a complete training course for detecting the changes in sensibility occasioned by new media.